Stock Market Integration as a part of Financial Market in the ASEAN Economic Community - Abimanyu, Yoopi (Jurnal Kajian Ekonomi dan Keuangan, 2015)
This paper is trying to assess whether the stock market in the Association of Southeast Asian Nations (ASEAN) countries, among others Indonesia, Thailand, Singapore, Philippine, Malaysia, and Vietnam, are integrated monthly data from January 2000 until August 2014. To support that analysis, a somewhat similar approached is done for the foreign exchange market in the same ASEAN member countries. The empirical results suggest that the ASEAN stock markets are co-integrated (except Philippines). Also, there is a positive relationship between Indonesia's and other ASEAN member countries' foreign exchange market. Those analysis were done in relationship with the new regional condition, faced by the new government just recently elected, that is, the ASEAN common market, which would be implemented in 2015.